2019
DOI: 10.1080/03019233.2018.1538179
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution behaviour of limestone in converter slag: evolution of microstructure and reaction interface

Abstract: The dissolution behaviour of limestone in converter slag at 1300-1400°C was studied, and the effects of the slag temperature and basicity were examined. The results showed that the increment of slag temperature was favourable to the formation of cracks and macropores in the generated lime, and the dissolution of the lime into liquid slag was promoted by the slag penetrating through these cracks and macropores. While the slag basicity increased from 0.5 to 1.0, the 2CaO•SiO 2 phase gradually formed around the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Different from the lime sample without CaCO 3 , dissolution of lime sample bearing CaCO 3 begins to accelerate after 60s and is faster than lime sample without CaCO 3 (Figure 4), which shows the expected results due to self-disintegrating effect sourced from CaCO 3 core decomposition [1820]. Mao et al have confirmed that the CO 2 generated by limestone decomposition can destroy the high-melting point 2CaO·SiO 2 layer, promoting the dissolution of limestone [18].…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Different from the lime sample without CaCO 3 , dissolution of lime sample bearing CaCO 3 begins to accelerate after 60s and is faster than lime sample without CaCO 3 (Figure 4), which shows the expected results due to self-disintegrating effect sourced from CaCO 3 core decomposition [1820]. Mao et al have confirmed that the CO 2 generated by limestone decomposition can destroy the high-melting point 2CaO·SiO 2 layer, promoting the dissolution of limestone [18].…”
Section: Resultsmentioning
confidence: 88%
“…The formed CO 2 gas by limestone decomposition can destroy the dicalcium silicate reaction layer at the slag/lime interface, thus, which can speed up the mass transfer of lime dissolution during limestone slagging mode [18]. Furthermore, the decomposition of limestone will cause cracks and pores in the decomposed lime layer, and more cracks would be formed with the increase of temperature in the range of 1300–1400°C [18,20]. In this paper, the self-disintegrating effect is defined as the phenomenon that the CO 2 gas generated from decomposition of limestone leads to the destruction of the dicalcium silicate interface layer and formation of cracks and pores in the decomposed lime layer.…”
Section: Introductionmentioning
confidence: 99%
“…However, the slag composition will be calculated based on the amount of flux melted. Many scholars have studied the dissolution behavior of lime in the converter melt pool [25][26][27][28]. Figure 4 shows the schematic diagram of the lime-melting process.…”
Section: Calculation Of Steel Slag Quantitymentioning
confidence: 99%
“…The dissolution mechanisms of CaO- and MgO-based carriers in the slag have been of great interest to the steel industry and a topic of investigations for decades [1–26]. Various oxidic and carbonaceous fluxes are used to create a slag.…”
Section: Introductionmentioning
confidence: 99%